Perioperative multimodal analgesia: a review of efficacy and safety of the treatment options - Kianian, Sara; Bansal, Jahnvi; Lee, Christopher; Zhang, Kalissa; Bergese, Sergio D. (ANESTHESIOLOGY AND PERIOPERATIVE SCIENCE, 2024)
Pain in the postoperative period is a common patient experience that can subsequently lead to other postoperative complications if not managed appropriately. While opioids are a common pharmacologic tool for managing pain, there are risks associated with liberal opioid use. Multimodal analgesic strategies, however, can adequately manage postoperative pain and minimize the risks associated with opioids. In this review, common pharmacological treatments for multimodal analgesia will be reviewed for efficacy, risks, and benefits, including gabapentinoids, opioids, alpha-2 agonists, ketamine, Non-steroidal anti-inflammatory drugs (NSAIDs) and corticosteroids. While this may not be a comprehensive list of medication options, it represents some of the most commonly used pharmacologic techniques for managing pain in the perioperative period. In addition, newer regional anesthetic techniques will be discussed to review their efficacy, risks, and benefits as well. The goal of this review is to summarize the various options for a multimodal analgesic protocol that we encourage providers to utilize when managing postoperative pain to facilitate conservative opioid usage and improve patient outcomes overall. Graphical Abstract